An Interface Design for Axial Induction Motor - Erkan Er; Mehmet Tahir güllüoğlu (International Journal of Trends in Mathematics Education Research, 2020)
Asynchronous motors have been used extensively in the industry since the first discovery. Although the general working principles do not change, they can be made geometrically in the form of cylinders, spheres, cones and even discs. One of these geometries is known as axial flux machine topology which has a disc structure. Axial flux machines are remarkable in terms of their high efficiency, high power density and advantage in terms of compact structures. In this study, extended literature search of axial flux induction motor is given. In addition to the literature, axial induction motor design interface has been created by using MATLAB GUI software. This interface can communicate with ANSYS Maxwell. Thus, the dimensioning values of the machine calculated via the interface can be drawn automatically in Ansys Maxwell and it can perform numerical analysis. The obtained torque, current and efficiency data were evaluated.